Comparação de indicadores de eficiência energética e exergética em duas indústrias do setor sucroalcooleiro - Schirmer, Florian (2006)
This work has an objective to study and to compare energetic and exergetic indicatives of two sugar and alcohol sector industry. The study was realized in 2005 harvest time at both industries. It was opted in doing the experiment collecting datas from individual boilers in each industry, quantity of ground cane, properties of cane and bagasse, quantity of energy involved in process per sectors, commercialized energy with the concession of each region and characteristics of each equipment involved in the process. The data were collected from respective department data-bank and through interviews with the responsibles for each sector, being the work based on studies done by diary and monthly average from collected data. The results pointed that each analyzed industry has different indicators for each studied data. The study states that both factories need more efficient equipments. And exergetic indicators presented results next to the studies done to Vale do Rosário Factory and mentioned on this work.